ASYMMETRIC CYCLES IN THE RHAETIC FACIES OF SOUTHERN ALPS: PLATFORM-BASIN INTERACTIONS GOVERNED BY EUSTATIC AND CLIMATIC OSCILLATIONS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The Rhaetic facies, as developed in the Southern Alpine region of Italy, were deposited in a strongly subsiding, fault-dissected trough (the Lombardian Basin) bounded by carbonate platforms. The main part of the Rhaetic succession consists of decametric scale, stacked asymmetric cycles, each divided into three parts: a lower shale portion, a central rhytmic portion consisting of repeated marl-limestone couplets, the limestone part of which gradually thickens upward, and a wholly carbonate upper unit. A study of the diagenetic history demonstrates that these marl-limestone alternations are fundamentally depositional in origin. This decametric cyclicity is identified as deriving from the superposition of a lower frequency (period of about 100,000 years) asymmetric carbonate mud signal with a high frequency sinusoidal argillaceous mud signal. Evidence is produced indicating that the basinal carbonate mud is predominantly allochthonous in origin, having been derived from the adjacent carbonate platforms. The associated asymmetric carbonate signal was a response to eustatic fluctuations which affected the characteristics of the subtidal "carbonate factory" in the platformal areas. These fluctuations are indicated by the repeated direct subaerial exposure of subtidal muds in shallow areas. The basinward exportation of carbonate muds was negligible in the deepening phase, increased during the shallowing evolution and was finally stopped by the emersion of large platformal flats. In contrast, the higher frequency argillaceous mud signal was probably climatically modulated; fluctuations of a higher frequency than those defined in Milankovitch theory affected hinterland precipitation and run off. The rapid subsidence and depositional rates allowed the preservation of this effect.
Keywords: Cyclicity; Eustasy; Paleoclimatology; Rhaetic; Upper Triassic; Southern Alps.